(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2014)
Feeding people means producing population. Biotechnology, encompassing food production as well as assisted reproductive technology (ART), currently emerges as a most important apparatus (dispositif) of governing populations. It should be understood as a means of “biopower” because it not only contributes to reproducing life but also helps to improve and preserve it. Highly depending on refrigeration, modern biopower invents a new type of life, which is technologically self-sustained. Therefore, sustainability is not only a question of “protecting the environment” but also of developing and maintaining an environment that allows us to dispose life: this is the cryogenic culture. In our paper, we trace the emergence and dissemination of what we call cryogenic life– meaning the ways of producing, distributing, maintaining and dispositioning organic matter via cooling, chilling and freezing. With the introduction of artificial coldness in the late 19th century and the expansion of the cold chain, these techniques have become a constitutive element of modern biopower. Today, it seems that nearly every aspect of life is affected by cryogenic techniques: we cool our food, environments, drugs, organs, eggs, milk, semen, tissue, blood and much more. Our central argument is that these developments lead to the formation of a new form of life, which in many ways is the antipode of what Agamben calls bare life. In analysing the emergence of cryogenic culture from a biopower point of view, this study offers a new perspective on how populations are fostered and governed through regimes of freshness. While the history of chilled and frozen food slowly gains increasing attention in historical and cultural studies, the historical dynamics of the cryopolitical economy in the network society still need to be explored.